Dictatorship, salmon farming and tourism: the expansion of the commodity frontier in northern Chilean Patagonia. Palena and Aysén (1973-1990) (Historia Agraria de América Latina, 2025)
This article analyzes the expansion of the commodity frontier in northern Chilean Patagonia (Palena and Aysén provinces) in the context of the military dictatorship and neoliberal reforms (1973-1990). From this analysis, we present the particular combination of State and capitalism that characterizes this historical process, in which this territory is defined as an empty space and its occupation is imposed through economic activities of transnational projection, such as salmon farming and tourism. Both processes lead to a complex commercialization of local water resources and a new tourist valuation of nature. The article is based on a geographic-historical approach and a qualitative methodology of content analysis, in which the propositional content of archives and documents of key institutions of this process (ODEPLAN, SERPLAC, CORFO, IREN-CIREN, Fundación Chile) is analyzed.
Keywords: Commodity frontier; Chilean Patagonia; Dictatorship; Salmon farming; Tourism